Nurses’ Life Experiences as Persons in Charge of Mental Health Programs in Community Health Center - Habsyah Saparidah Agustina; Suryani Suryani; Efri Widianti (Jurnal Keperawatan Padjadjaran, 2019)
At present, Mental health issue becomes one of the main issues in public health issues in community health centers such as the complexity of the issues in the work of nurses in charge of mental health programs. The purpose of this study was to explore the nurse’s life experience as a person in charge of mental health programs in community health centers. The research design used descriptive phenomenology. The study population was nurses responsible for mental health programs in community health centers, experienced in taking care of people with mental disorders for at least six months, and at least had a Diploma in nursing.  The number of participants was determined by purposive sampling technique to obtain seven participants. The experiences of nurses were explored through in-depth interviews, and data were analyzed using the Colaizzi method of analysis. Study results found five themes: (1) feeling burdened by the responsibility for mental health programs; (2) feeling insecure due to the lack of knowledge; (3) feeling there were many barriers and constraints in caring for people with mental illness during the recovery period; (4) hoping to collaborate with relevant government institutions; and (5) being more grateful for caring for people with mental illness.  In conclusion, nurses are responsible for mental health programs even though they feel burdened with their workload, but they can still do their jobs because they always have hope and are grateful. The nurses are trained nurses and can collaborate with relevant government institutions.